Futsal Faststart: The development of a Futsal-specific warm-up - Tomsovsky, L.; Reid, D.; Whatman, C.; Fulcher, M.; Walters, S. (New Zealand Journal of Sports Medicine, 2020)
Aim: To develop a futsal-specific warm-up for recreational futsal players using a focus group approach. Study Design: Two phases; i) two focus groups with sport medicine professionals, futsal coaches and players, ii) the development of a new, futsal-specific warm-up (Futsal FastStart). Setting: New Zealand futsal environment. Participants: Sport medicine professionals, futsal coaches and players. Main Outcome Measures: The development of a new warm-up for recreational futsal via two focus groups. The concepts of warming up in the futsal environment were evaluated using a thematic analysis. Results: Six futsal players and coaches, and four sport medicine professionals agreed that a warm-up was important to reduce injuries. The issues of time and space available to warm up were highlighted. Warming up as a team and incorporating a ball was suggested to improve compliance. The 11+, an injury-prevention warm-up used in football, was considered an adequate cornerstone from which to develop a new, futsal-specific warm-up (Futsal FastStart) to target futsal injuries. Conclusions: Input from key stakeholders enabled the development of a new, futsal-specific warm-up for recreational players. Including futsal players and coaches in the design should enhance delivery and adherence to the warm-up. However, whether this warm-up has any impact on IP has yet to be determined.